ANALYSIS OF STONE COLUMN IN SOFT SOIL BY FINITE ELEMENTS METHODS - A. Al Hity, Ahmed (Iraqi Journal of Civil Engineering, 2007)
This paper includes an analysis to asses the behavior of stone columns using the finite element method and to provide bases and information helping geotechnical engineers to design foundations resting on weak soils reinforced with stone column. The axisymmetric quadrilateral element is adopted in the finite element program to simulate the soft soil and the stone column while the one-dimensional element is used to simulate the soft soil and the stone column-soil interface. The nonlinear inelastic stress-dependent model is used to simulate the behavior of the soil and the interface throughout the incremental loading stages adopting nonlinear parameters obtained from triaxial and direct shear stress. The analysis is carried first on a selected basic problem, to clarify the nonlinear of the column, in which a selected geometry, boundary condition, and material properties for both soil and interface as chosen. The rest of the analysis is grouped into the effect of some of the parameters concerning the geometry of the stone column and the material of column and adjacent soil are investigated. It was found that the increase in stone column length and in relative stiffness of stone column material to soil play an important role in increasing ultimate capacity of the stone column and in reducing settlements.